Takayasu's arteritis: What should the dentist know? - Duque, Cristiane [UNESP]; Silva, R. C.; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (Wiley, 2005)
Takayasu's arteritis is a chronic inflammatory disease that affects large blood vessels, especially the aorta and/or its major branches. The condition presents with segmental lesions adjacent to normal, apparently unaffected, areas. The lesions include stenosis, occlusion, dilatations or aneurysm formations along the path of the affected artery. Because of the severity of the disease and the possibility of cardiovascular complications, patients with Takayasu's arteritis require medical treatment based on immunosuppressive and antihypertensive drugs, as well as regular follow up and surgical intervention in many instances. The aim of this paper was to describe the characteristics of Takayasu's arteritis, to report dental treatment carried out on an affected patient, and to discuss the main implications and care required during routine treatment for children in the dental office. © 2005 BSPD and IAPD.
Keywords: amoxicillin; calcium carbonate; corticosteroid; folic acid; methotrexate; prednisone; propranolol; ranitidine; anamnesis; aorta arch syndrome; case report; dental care; dentistry; human; male; medical examination; pyoderma gangrenosum; school child; Amoxicillin; Anesthetics, Local; Antibiotic Prophylaxis; Child; Dental Calculus; Dental Care for Children; Dental Care for Chronically Ill; Dental Caries; Felypressin; Gingivitis; Humans; Male; Prilocaine; Takayasu's Arteritis; Vasoconstrictor Agents